Management of Serrated Polyps of the Colon - Fan, Claire (Curr Treat Options Gastroenterol, 2018)
PURPOSE OF REVIEW: The purpose of this review is to summarize the management of serrated colorectal polyps (SPs), with a particular focus on the most common premalignant SP, sessile serrated adenoma or polyp (SSA/P). These lesions present a challenge for endoscopists with respect to detection and resection, and are also susceptible to pathologic misdiagnosis. RECENT FINDINGS: Patients with SSA/Ps are at an increased risk of future colorectal neoplasia, including advanced polyps and cancer. Reasonable benchmarks for SP detection rates are 5–7% for SSA/Ps and 10–12% for proximal SPs. Certain endoscopic techniques such as chromoendoscopy, narrow band imaging, water immersion, and wide-angle viewing may improve SSA/P detection. Emerging endoscopic techniques such as underwater polypectomy, suction pseudopolyp technique, and piecemeal cold snare polypectomy are helpful tools for the endoscopist’s armamentarium for removing SSA/Ps. Proper orientation of SSA/P specimens can improve the accuracy of pathology readings. Patients with confirmed SSA/Ps and proximal HPs should undergo surveillance at intervals similar to what is recommended for patients with conventional adenomas. Patients with SSA/Ps may also be able to lower their risk of future polyps by targeting modifiable risk factors including tobacco and alcohol use and high fat diets. NSAIDs and aspirin appear to be protective agents. SUMMARY: SPs and SSA/Ps in particular are important colorectal cancer precursors that merit special attention to ensure adequate detection, resection, and surveillance.